A Fraternidade como categoria política: princípio anunciado na educação brasileira - Torres, Ivanna Sant'Ana (2010)
This dissertation has had the goal of understanding and discussing how the fraternity category is presented in the main Brazilian education laws after the promulgation of the 1988 Federal Constitution. The systematization of a theoretical base about the fraternity category in its relation with de Brazilian education regulatory landmarks has allowed the proposition of elements of this category. The process of building the theoretical references of this research was written from a historical recuperation of the French Revolution, taking into account the triad of its main principles, “liberty, equality, and fraternity”, as civic and political values. Likewise, the Haitian Revolution was considered because of the symbolic role this revolution played on the concretization of the triad through the slave and black people’s struggle whose aims were both participation in the colony’s power positions and in the abolishing of slavery. The modernity and post modernity issues, as well as the concepts of citizenship and human rights, are also took as theoretical references in order to identify characteristics and connections of each one of those themes and concepts with the fraternity as a political category. This analysis has allowed the elaboration and systematization of the fraternity category and its constitutive elements: the universality which is directly connected to the local and regional issues; the mondialization as a counter-argument to the globalization which is seen exclusively in its economic dimension; the participative democracy as alternative way to the representative democracy; the “alteridade” (a kind of altruism) due to its specific way to recognize the other one as someone pretty much like me; and the diversity which consider the multicultural perspective and the necessity of building unity. It was possible to identify that the first two elements of the triad, liberty and equality, were the most import ones over the so called modernity period when the triad was put in the second place or only in its religious dimension. The post modernity, in turn, has brought to light the fraternity due to its constitutive elements. It was also possible to highlight the citizenship as a modernity landmark and the human rights as an idea marked by the fraternity and directly linked with the post modernity. From this theoretical frame it was made an analysis of the legal instruments that organize and regulate the Brazilian education: the 1998 Federal Constitution; the Statute for Children and Adolescents; the National Brazilian Education Law; and the National Education Plan. All these legal instruments were discussed based on their relation with the fraternity as a political category and through the identification of its main constitutive elements. The methodological way was put into practice mainly through the qualitative dimension, especially the Bardin’s content analysis. The dissertation has permitted to emphasize that the fraternity as political category was not a forgotten principle in the Brazilian education legislation, but a principle not formally and textually declared yet.